Reactive Arthritis by Intestinal Parasites in the Central Military Hospital in Lima - Feijóo Quiroz, Octavio (1999)
OBJECTIVE: To determine the causal relationship existent between intestinal parasitic infestations and reactive arthritis (ReA). MATERIAL AND METHODS: A case-control trial with patients admitted to the Hospital Militar Central of Lima, 31 of them were diagnosed as having ReA between 1994 and 1995 (control group) and 31 ReA-free patients. Data were obtained from medical records. RESULTS: In the case group, 11 patients (35,48%) had intestinal parasites; 12 (38,71%) presented albendazol- and/or metronidazol-sensitive eosinophilia decreasing with clinical improvement after treatment; and 8 (25,81%) had neither parasites diseases nor eosinophilia. In the control group, the distribution was 7 (22,58%), 5 (16,13%) and 19 patients (61,29%), respectively. CONCLUSION: We found a strong correlation between intestinal parasitic infestations and ReA (OR = 4,5; p <0,05), and parasitic infections may have a synergic arthritogenic effect. Ascaris lumbricoides (7/11) and Ancylostoma duodenale (5/11) were the commonest parasites.